Organ donation among community in Shah Alam Selangor, Malaysia / Noor Idzwannie Tumpanga, Mohd Ramlan Mohd Arshad and Nur Syafiqah Abd Rahman - Tumpanga, Noor Idzwannie; Mohd Arshad, Mohd Ramlan; Abd Rahman, Nur Syafiqah (Universiti Teknologi MARA, 2020)
The aim of this study is to explore the perception of community on organ donation. The main objectives are to explore the relationship between the variables namely attitude, family influence, religious belief and mass media also derive the main antecedent that may shape the community perception on organ donation. This study also generated the difference of the view on organ donation between genders. 384 respondents of this study are community lived in Shah Alam, Selangor, Malaysia. Purposive sampling technique was used with questionnaire as the instrument. Correlation and Independent Sample T-Test analysis were conducted, and the findings show that there is a significant relationship between the variables and perception on organ donation with religion belief as the main factor. T-Test shows that there is no significant difference between male and female for their insights belief on organ donation. Hence, various parties such as authority, non-governmental bodies and community has benefited from the study.